2021
DOI: 10.3389/fnins.2021.648143
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Functional Connectivity Reveals Abnormal Variability in the Amygdala Subregions of Children With Attention-Deficit/Hyperactivity Disorder

Abstract: Objective: This study investigates whether the dynamic functional connectivity (dFC) of the amygdala subregions is altered in children with attention-deficit/hyperactivity disorder (ADHD).Methods: The dFC of the amygdala subregions was systematically calculated using a sliding time window method, for 75 children with ADHD and 20 healthy control (HC) children.Results: Compared with the HC group, the right superficial amygdala exhibited significantly higher dFC with the right prefrontal cortex, the left precuneu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 82 publications
3
8
0
Order By: Relevance
“…We should note that several studies have indicated precuneus abnormalities was involved in both ADHD and ASD, however with the same effect direction [53,54], which pushed us to enroll typically developing children with ATs in our further study to con rm the acute effect direction of the shared cluster of right PL/precuneus on ADHD and ATs. For the left PL/precuneus, the mALFF alterations was ADHD-speci c, which was consistent with that reported previously [55]. Together with the right caudate nucleus, left precuneus can classifying ADHD from normal groups with 62.52% accuracy [56].…”
Section: Discussionsupporting
confidence: 87%
“…We should note that several studies have indicated precuneus abnormalities was involved in both ADHD and ASD, however with the same effect direction [53,54], which pushed us to enroll typically developing children with ATs in our further study to con rm the acute effect direction of the shared cluster of right PL/precuneus on ADHD and ATs. For the left PL/precuneus, the mALFF alterations was ADHD-speci c, which was consistent with that reported previously [55]. Together with the right caudate nucleus, left precuneus can classifying ADHD from normal groups with 62.52% accuracy [56].…”
Section: Discussionsupporting
confidence: 87%
“…A meta-analysis by Kofler et al (2013) revealed that children and adolescents (Hedges’ g = 0.76) and adults (g = 0.46) with ADHD demonstrated greater variability relative to control groups (results were corrected for measurements of unreliability and publication bias) [ 16 ]. However, recent studies also introduced dynamic functional connectivity as a promising biomarker in the context of ADHD, suggesting new parameters to quantify the dynamics within and between networks such as recruitment rate, topology of specific synergies between resting-state networks and synergetic cooperation patterns [ 24 ] as well as using the sliding window approach in terms of time-varying covariance of interregional neural signals [ 53 ]. A wavelet-based parameter like wVar, thus, adds valuable information to the current scientific debate to rather focus on dynamics in fMRI than static parameters in ADHD patients.…”
Section: Resultsmentioning
confidence: 99%
“…Using the DynamicBC toolbox (Liao et al, 2014 ), the sliding window method was used to analyze the dFC for each participant. According to previous research, the window length is an open but important parameter in sliding window based resting state dynamic computation (Fateh et al, 2020 ; Li et al, 2020 ; Yang et al, 2021 ). This approach can calculate the time-varying covariance of interregional neural signals, which is the variance of dFC, and reveal the temporal aspects of FC during the full scan period.…”
Section: Methodsmentioning
confidence: 99%
“…Sun et al ( 2021 ) suggested state-dependent dynamic changes in large-scale brain connections and network topologies in ADHD. Yang et al ( 2021 ) found that children with ADHD have more unstable dFC of the amygdala subregions, which may impact their cognitive skills. As a result, it should be indicated that to ensure successful diagnosis, therapy, and prevention, it is critical to research the sophisticated mechanisms underlying ADHD, as well as the functional deficits of the diseased brain.…”
Section: Introductionmentioning
confidence: 99%